Subcutaneous expanders and synthetic mesh for breast reconstruction: Long-term and patient-reported BREAST-Q outcomes of a single-center prospective study. Issue 5 (May 2019) - Casella, D.; Di Taranto, G.; Marcasciano, M.; Lo Torto, F.; Barellini, L.; Sordi, S.; Gaggelli, I.; Roncella, M.; Calabrese, C.; Ribuffo, D.
Summary: Recently, prepectoral breast reconstruction is experiencing a revival. Despite the growing body of early reports about subcutaneous breast reconstruction, literature lacks in long-term results and studies focusing on patient-reported outcomes and health-related quality of life. Between January 2012 and December 2016, patients undergoing mastectomy were enrolled at our institution. We selected patients diagnosed with breast cancer or genetic predisposition to breast cancer, undergoing conservative mastectomy, either nipple-sparing or skin-sparing mastectomy, and willing for prepectoral tissue expander reconstruction assisted by a synthetic mesh. Exclusion criteria were body mass index greater than 35 kg/m 2 and pregnancy. BREAST-Q questionnaire was administered prior to surgery and after 1 year. Capsular contracture was evaluated using Baker scale. Oncological, surgical, and esthetic outcomes along with the changes in BREAST-Q score were analyzed over time. One hundred eighty-seven patients were enrolled, with an average age of 55.5 years. One hundred thirty-seven unilateral mastectomy and 50 bilateral mastectomy procedures were performed, accounting for a total of 237 operated breasts. The average follow-up period after the second stage was 36.5 months. Postoperative complications that require a second operation occurred in 16 cases (6.7%) (4 wound dehiscence, 2 skin–nipple necrosis, 7 infections, and 3 seroma cases). A locoregional recurrence occurred in 3 cases (1.9%) and a systemic recurrence occurred in 2 cases (1.3%). Patients scored high level of satisfaction with outcome. Overall satisfaction with breasts, psychosocial well-being, and sexual well-being was all significantly increased after the surgery ( p < 0.05). Two-stage expander reconstruction technique provides the preservation of the pectoralis major muscle with an acceptable rate of complications. We confirm satisfactory patient-reported and esthetic results, with high patient comfort.